Spatial organisation of an ecological niche of the urbozem mesofauna - O. Y. Pakhomov; O. М. Kunah; O. V. Zhukov; Y. A. Balyuk (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Bìologìâ, Ekologìâ, 2013)
Study results of the spatial organisation of urbozem mesofauna are presented. We used the OMI-analysis methods. Field research was made in June, 1st, 2011 inthe Botanical Gardenof Dnipropetrovsk National University(DNU) (earlier – the territoryof Y. Gagarinpark, Dnipropetrovsk). The studied plot is situated at a distance of 220 mfrom the Building 1 of DNU and at a distance of 60 mfrom Y. Gagarin Avenue(the Southeast direction). The plot consists of 15 transects directed in a perpendicular manner in relation to the Avenue. Each transect is made of seven sample points. The distance between points is 2 m. The coordinates of lower left point have been taken as (0; 0). The plot represents artificial forest-park planting. The vegetation has typically wood mesotrophic mesophilic character (93.3% – silvants, 90.0% – mesotrophes, 81.7% – mesophiles). In each point the soil mesofauna was studied; temperature, electrical conductivity and soil penetration resistance, dead leaves layer and herbage height were measured. Soil-zoological test area had a size of 25 × 25 cm. We found that earthworms are numerous and saprohages are presented by 5 species. The Aporrectodea caliginosa trapezoides (Duges, 1828) is a dominant species. Along with that species an ecological group of endogeic earthworms is presented by A. rosea rosea (Savigny, 1826) and Octolasion lacteum (Oerley, 1885). An ecological diversity of earthworms is supplemented by epigeic Lumbricus rubellus Hoffmeister, 1843 and anecic Octodrilus transpadanus (Rosa, 1884). The hygromorphs of earthworms range from ultrahygrophiles to mesophiles. The coenomorphic spectrum of earthworms is also rather wide and presented by “pratants”, “stepants”, “palludants” and “silvants”. The complex of earthworms in studied area is taxonomically and ecologically diverse. The ecological structure of soil animal community is presented by such dominant ecological groups as saprohages, pratants, hygrophiles, mesotrophocoenomorphs, and endogeic topomorphs. The measured soil characteristics have been shown to play an important role in structuring an ecological niche of mesopedobionts community. The basic trends in structure transformation of the soil mesofauna community are ecotone effect and edaphic properties determined by a vegetation cover.